Broad Search of Better Thermoelectric Oxides via First-Principles Computations. Issue 1774 (2015) - Hao, Qing; Zhao, Hongbo; Lu, Na
ABSTRACT: The advancement of computational tools for material property predictions enables broad search of novel materials for various energy-related applications. However, challenges still exist in accurately predicting the mean free paths (MFPs) of electrons and phonons in a high-throughput frame for thermoelectric property predictions, which largely hinders the computation-driven search for novel materials. In this work, this need is eliminated under the small-grain-size limit, in which these MFPs are restricted by the grain sizes within a bulk material. A new criterion for ZT evaluation is proposed for general nanograined bulk materials and is demonstrated with representative oxides.